2014
DOI: 10.1002/jrs.4581
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy at different excitation wavelengths (1064, 785 and 532 nm) as a tool for diagnosis of colon cancer

Abstract: Raman spectroscopy is structure sensitive non‐destructive method that allows observing the status of biological tissues with minimal impact. This method has a great potential in the diagnosis of various types of degenerative diseases including cancer damages. Near‐infrared Fourier transform (NIR‐FT)‐Raman (λex ~1064 nm), NIR‐visible (Vis)‐Raman (λex ~785 nm) and Vis‐Raman (λex ~532 nm) spectra of normal and colorectal carcinoma colon tissue samples were recorded in macroscopic mode at 10–20 randomly chosen ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 60 publications
2
52
0
1
Order By: Relevance
“…Figure 7a, brown bars are indicated on the peak, which is the main factor above the graph drawn as the average of total data. The main peaks for the control and IP/BPS samples were observed at 641, 683, 723, 873, 1002, 1030, and 1355 cm −1 , which corresponded to C-C twisting mode of tyrosine [37,38], ring breathing of nucleic acids for G [38,39] and A [39,40], C-C stretch of hydroxyproline [37,41], symmetric ring breathing mode [37][38][39][40][41] and C-H in-plane bending mode of phenylalanine [37,41], and CH 3 CH 2 wagging mode of collagen [37,41], respectively.…”
Section: Bio-applicationmentioning
confidence: 98%
“…Figure 7a, brown bars are indicated on the peak, which is the main factor above the graph drawn as the average of total data. The main peaks for the control and IP/BPS samples were observed at 641, 683, 723, 873, 1002, 1030, and 1355 cm −1 , which corresponded to C-C twisting mode of tyrosine [37,38], ring breathing of nucleic acids for G [38,39] and A [39,40], C-C stretch of hydroxyproline [37,41], symmetric ring breathing mode [37][38][39][40][41] and C-H in-plane bending mode of phenylalanine [37,41], and CH 3 CH 2 wagging mode of collagen [37,41], respectively.…”
Section: Bio-applicationmentioning
confidence: 98%
“…24 785 nm laser excitation was purposely chosen for Raman spectroscopy, since it offers an excellent balance between Raman efficiency, sample fluorescence, and heat absorption. 25 Although the maximum LSPR peak is far from our excitation wavelength, components in the blood plasma (such as proteins, analytes, and salts) can contribute to the analyte-colloid and colloid-colloid interactions, which finally cause nanoparticles to aggregate, resulting in a red-shift of the LSPR. 26 This phenomenon can be easily confirmed by plotting the absorption spectra with different volume ratios of blood plasma and concentrated AgNPs (see Figure S3).…”
Section: Optimization Of Sers Signalsmentioning
confidence: 99%
“…Principal component analysis (PCA), a frequently used unsupervised approach, reduces the number of variables and assesses the data as a first step. Following PCA, a supervised approach such as linear discriminant analysis (LDA), which takes advantage of PCA and the histopathological results, can classify tissues or cells [12][13][14]. A study on mice with colon cancer showed that the PCA-LDA model can correctly discriminate tumors from healthy tissues with an accuracy of 86.8% [15].…”
Section: Introductionmentioning
confidence: 99%